ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MAHASISWA DALAM PENYUSUNAN DESAIN PEMBELAJARAN IPA TERPADU MODEL ROBIN FOGARTY - Anriani, Titi; Rohmi, Puspo; Sabarudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the critical and creative thinking skills of students as future teachers in designing integrated science learning using the Robin Fogarty model. This study uses a qualitative approach with a descriptive method. This research was conducted at UIN Sunan Kalijaga from October to November 2024. The subjects of the study were lecturers and students. Data were collected from two main sources, namely primary data and secondary data. The data for this study were obtained in three ways, namely observation, interviews, and documentation. Data analysis through data collection, data presentation, data conclusion/verification, and condensation process. The data that has been analyzed will be tested for validity using data triangulation. This study shows that students already have quite good critical thinking skills, but their creative thinking skills still need to be improved. Although students can analyze information, draw conclusions, and present logical arguments, they still have difficulty producing original and diverse ideas. Some of the obstacles students face include difficulty in determining the theme of integrated learning, lack of in-depth understanding of concepts, and lack of experience in designing learning. The results of this study highlight the importance of providing more intensive training to students in developing creative thinking skills and integrated learning design skills.